Antioxidant Supplementation Improves Lipid Profiles and Antioxidant Levels in Post-menopausal Women: Systematic Review and Meta-Analysis - Tandiono, Felicia; Apriliani, Dyang Wulan; Safitri, Fadhila Permata; Gerardo, Timothy Sahala; Tarigan, Audrey Gracielle (Asian Journal of Health Research, 2025)
Introduction: Post-menopause is marked by a decline in estrogen levels around age 50, leading to unfavorable metabolic changes, including increased LDL-c and decreased HDL-c, which elevate cardiovascular disease (CVD) risk. Reduced antioxidant capacity during this phase also heightens oxidative stress, contributing to chronic diseases such as CVD, osteoporosis, and cancer. Given the limitations of conventional treatments, antioxidant supplementation has emerged as a potential alternative.   Material and Methods: Systematic Reviews and Meta-Analyses Preferred Reporting Items (PRISMA) framework was used in this study. Studies on arterial ligation techniques in placenta percreta surgery were included based on criteria focusing on estimated blood loss, operative time, and adverse events. A comprehensive literature search across multiple databases was performed, resulting in three studies that met the inclusion criteria.    Results: The three studies included in the review with a total of 193 patients. The findings show that IIAL significantly decreased the projected amount of blood loss compared to control groups. In one study, bilateral IIAL showed lower blood loss (1076 ± 545 ml) compared to other interventions, while another study demonstrated that IIAL resulted in lower estimated blood loss compared to control groups. However, hypogastric artery ligation (HAL) was associated with higher blood loss in one study. Despite its effectiveness in controlling blood loss, complications such as common iliac artery thrombosis, pseudoaneurysms, and limb ischemia were reported, though with low incidence.    Conclusion: Arterial ligation, particularly IIAL, could be a viable strategy for managing blood loss during placenta percreta surgery.